2019
DOI: 10.1002/cncr.32484
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of opioids with benzodiazepines or nonbenzodiazepine sedatives among patients with cancer referred to an outpatient palliative care clinic

Abstract: Background The concurrent use of opioids with benzodiazepines (BZD) or nonbenzodiazepine sedatives (S) recently was found to be associated with an increased risk of overdose death compared with the use of opioids alone. In the current study, the authors examined the frequency and trend of concurrent opioid/BZD‐S use and its associated risk factors among patients with cancer. Methods Data regarding the frequency and trend of concurrent opioid/BZD‐S use were extracted for 1500 randomly selected patients referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Given that there is no international standard for measuring the level of hospital opioid consumption, comparisons were made between our collected data and existing foreign published studies on drug utilization and opioid consumption evaluations in hospital settings based on the ATC/DDD system. We confirmed the hypothesis of our study, that is, opioid consumption at this hospital was relatively low compared with the consumption rates reported in other studies, which included two hospitals and four databases from Europe, East Asia, and North America (12)(13)(14)(15)(16)(17). One study using the same measurement unit (DDD/100 bed-days), carried out in a hospital in Madrid, Spain, revealed that opioid consumption had a remarkable increasing tendency, from 22.3 DDD/100 bed-days in 2011 to 26.5 DDD/100 beddays in 2015 (16).…”
Section: Discussionsupporting
confidence: 91%
“…Given that there is no international standard for measuring the level of hospital opioid consumption, comparisons were made between our collected data and existing foreign published studies on drug utilization and opioid consumption evaluations in hospital settings based on the ATC/DDD system. We confirmed the hypothesis of our study, that is, opioid consumption at this hospital was relatively low compared with the consumption rates reported in other studies, which included two hospitals and four databases from Europe, East Asia, and North America (12)(13)(14)(15)(16)(17). One study using the same measurement unit (DDD/100 bed-days), carried out in a hospital in Madrid, Spain, revealed that opioid consumption had a remarkable increasing tendency, from 22.3 DDD/100 bed-days in 2011 to 26.5 DDD/100 beddays in 2015 (16).…”
Section: Discussionsupporting
confidence: 91%
“…59 Our larger, nationally representative sample found a higher rate (25%) of benzodiazepine coprescribing during LTOT among breast cancer survivors, and this elevates concern for this population. A study by Haider et al 60 found that 31% of patients with cancer receiving opioids in a palliative care clinic also received benzodiazepines. Similarly to our findings, Haider et al found higher rates of coprescribing of benzodiazepines and opioids among patients with anxiety and depression, and this reflected the use of benzodiazepines to manage these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Note US FDA warning of the risk of serious breathing difficulties in patients taking central nervous system depressants (including opioids) concurrently with gabapentin or pregabalin (34) Concurrent use of gabapentin has been associated with an increased risk of opioid-related death (35) Concurrent use of benzodiazepines has been associated with up to 5-fold increased risk of opioid overdose-association death (36) Strong opioids Co-administration of pregabalin increases the risk of somnolence or dizziness vs. pregabalin alone (37) Morphine Morphine-induced gastrointestinal hypomotility may increase pregabalin absorption (37) Breakthrough pain -Cancer patients who are prescribed a baseline sustained-release opioid may also require an on-demand immediate-release opioid for rescue situations such as breakthrough pain (38,39) Inadequate analgesia and/or drug tolerance -For opioid rotation, consider a two-step dose-reduction and re-titration approach for adjusting to differences in side effects and pharmacokinetics (40,41) authors failed to find clinically relevant sex difference in opioid-induced respiratory depression. However, there were higher rates of respiratory events reported for five opioids in patients ≥70 years, underlining the need for careful dosing in older people.…”
Section: Age Gender Ethnicity and Psychologymentioning
confidence: 99%
“…The concurrent use of opioids with benzodiazepines, which is still common in cancer patients, has been associated with a risk of overdose-associated death up to 5-fold greater than for opioids alone (36).…”
Section: Risks Of Co-administration Of Opioids and Analgesic Adjuvantmentioning
confidence: 99%